Property Tax Decentralisation Program, Punjab, Pakistan : Business Blueprint - World Bank (Washington, DC, 2013)
Following a number of World Bank reports a new Punjab Immovable Property Tax Law (PIPT) was drafted in May 2008 and the Bank appointed the Institute of Revenues Rating and Valuation (IRRV) to assess the needs and resources required for the structural reform of the property tax. This blueprint is the outcome of that assessment. This document comprises of ten sections: introduction to the blue print (section one); the need for the change and the consequential vision, mission, and operating principles (section two); institutional and governance arrangements (section three); operational and organizational design (section four); human resources (section five); developing the property tax policy (section six); technology (section seven); core administration (section eight); customer services (section nine); program management (section ten); and appendix.